Traumatic Focal Pancreatitis with Retro-Duodenal Hematoma: A Rare Cause of Combined Biliary and Gastric Outlet Obstruction - Scalera, Irene; Kumar, Senthil; Bramhall, Simon (JOP. Journal of the Pancreas, 2012)
Context Focal post-traumatic acute pancreatitis causing combined duodenal and biliary obstruction is extremely rare. Case report A 16-year-old boy presented with acute upper abdominal pain which was clinically and biochemically consistent with mild acute pancreatitis. There was no etiological factor identified initially, although a history of blunt abdominal trauma was later discovered. He soon developed features of gastric outlet obstruction and obstructive jaundice over 48 hours. A CT scan showed a retroduodenal mass causing compression of both the duodenum and bile duct. At exploration, this was found to be a walled off hematoma. There was evidence of focal pancreatitis in the head of pancreas. Evacuation of the hematoma cured the gastric outlet and biliary obstruction. Conclusion The triad of pancreatitis, gastric outlet and biliary obstruction along with a mass lesion on cross sectional imaging in young adults should raise the suspicion of a hematoma as a probable cause. Image: CT scan of the abdomen showing a rounded heterogeneous mass compressing the second part of duodenum.